Development of Pancasila Student Profiles on the Mutual Assistance Character: Can Traditional Games through Socratic Method-based Learning Help? - Lutfi Nur; Dodi Suryana; Mesa Rahmi Stephani; Rangga Gelar Guntara; Fariha Nilan; Muhammad Rahmanda; Dede Akhmad Nawawi; Rudi Salam (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2022)
A character is a crystallization form of the habituation process carried out by individuals during their life spans. Character building is carried out firstly in the family environment and can be instilled through formal and informal educational institutions. Currently, the government is promoting character education and Pancasila students in schools because it is believed to shape child character effectively. This study aimed to improve elementary school students' gotong royong character, known as the mutual assistance character, through traditional games using Socratic method-based learning. This research is an experimental research using pre-experimental (single group designs). The participants were 37 elementary school students aged 9-11 years. The mutual assistance character was measured using a questionnaire instrument adapted from the Permendikbud and integrated with Krathwohl affective domain indicators. Data were analyzed using SPSS 21 employing paired sample T-test processing. The results show a significant increase from the pretest to post-test results (16.6% on mutual assistance, 18.1% on cooperation, and 15.1% on communication). It implies that traditional games through Socratic Method-based learning can be used as an alternative to developing the mutual assistance character as an effort to promote the profile of Pancasila students in elementary schools.